Assessing the Prospective Yield of Regional Trade in Sino-Pak Bloc, South Asia: Selected Manufacturing Sectors Analysis - Khan, Sidra Sarwar; Liaqat, Saima; Iqbal, Munawar; Riaz, Muhammad Farhan (iRASD Journal of Economics, 2023)
The study uses the Revealed Comparative Advantage method to assess Pakistan-China trade potential under the assigned FTA. For this purpose, secondary-level data was collected from UN-comrade from 2003-2018. Three major industries of the manufacturing sector (textile, food, leather) have been taken to check the effect of FTA on Pakistan-China trade. The results show that Pakistan has RCA in these three sectors, but still, its exports are lower than China; both Pakistan and China have the advantage of FTA, but China has more benefits. Because the effect of FTA is positive for China, Pakistan is enjoying very few benefits from these agreements.